Italo Svevo and the vexations of the "father" of the "Orlando Furioso": senility and madness in the "Ariosto governatore" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2025)
The essay analyses the “Ariosto’s function” within an unfinished early theatrical work by Italo Svevo. The text, generally not very studied, is of significant interest for investigating the vitality of the author of Orlando furioso well beyond his historical time. The analysis, after having focused on the painful editorial history of the fragment, identifies the crucial themes that this first literaryexperiment by Svevo recovers, rereading them in an original and personal key, from Ariosto’s great poem and from his so-called minor works.
Keywords: Ariosto's function; Old age; Madness; Love; Garfagnana